The Existence of Civil Sanctions in Spatial Law Enforcement in Indonesia - Siburian, Henry Kristian; Sipayung, Baren -; Andjarwati, Any -; Manulang, Sardjana Orba; Harahap, Muhammad Ade Kurnia (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Planning for territorial spatial arrangement is one of the problems with modern urban growth, as cities are growing faster than ever and the territorial government has to take a unique role in overseeing spatial arrangement. 2007 Law No. 26 The government is considering replacing Law Number 24 of 1992, which deals with spatial arranging, with this legislation, which unifies a courteous administration. This study's method of investigation was controlling valid research while taking the study's characteristics into account. The result of the review is the assertion that, taken as a whole, respecting legislation represents people's rights (personenrecht). of In particular, laws, customs, conventions, theories, and statutes give birth to two legitimate subjects: Separately, legal substances (rechts persoon) and humans (natuurlijke persoon). Articles 66, 67, and 75 of Law Number 26 of 2007 concerning Spatial Arranging provide certain limitations on the occurrence of generous fines. If the last stated are ultimum remedium in nature, a claim based on reclamation may be used to seek for polite discipline for spatial arrangement violations in addition to official and criminal penalties.